2010
DOI: 10.4314/ijest.v2i1.59107
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining fixture layout for tolerance requirements under the influence of locating errors

Abstract: Dimensional accuracy of workpart under machining is strongly influenced by the layout of the fixturing elements like locators and clamps. Setup or geometrical errors in locators result in overall machining error of the feature under consideration. Therefore it is necessary to ensure that the layout is optimized for the desired machining tolerance for a given deviation in the set up or geometry of the locator. Also, the locator layout should be capable of holding the workpart in a unique position during machini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Kedua penelitian tersebut tidak menggunakan programa matematika, tetapi menggunakan algoritma genetika (genetic algorithm). Serupa dengan kedua penelitian tersebut, Vishnupriyan, et al [12] melakukan optimasi tata-letak lokator untuk memenuhi kebutuhan toleransi yang dipengaruhi oleh kesalahan penempatan, menggunakan algoritma genetika.…”
Section: Pendahuluanunclassified
“…Kedua penelitian tersebut tidak menggunakan programa matematika, tetapi menggunakan algoritma genetika (genetic algorithm). Serupa dengan kedua penelitian tersebut, Vishnupriyan, et al [12] melakukan optimasi tata-letak lokator untuk memenuhi kebutuhan toleransi yang dipengaruhi oleh kesalahan penempatan, menggunakan algoritma genetika.…”
Section: Pendahuluanunclassified
“…The FEA predictions of workpiece deformationand locator reactions are experimentally verified [5].The layout of fixture including clamp and locator layout play an important role in fixture performance. Vishnuprian et al suggested fixture layout optimization by taking into consideration the effect locator errors.The study presented deterministic location ensured throughout the optimization process and minimal machining errors [6].…”
Section: Introductionmentioning
confidence: 99%
“…A Genetic Algorithm (GA) based optimization method is proposed to arrive at a layout of error containing locators for minimum machining error satisfying the tolerance requirements and providing deterministic location. This may be advantageous in cases where a less strict tolerance on locator is acceptable thus reducing the cost of manufacture of locators (Vishnupriyan et al 2010)…”
Section: Introductionmentioning
confidence: 99%